MINANG CULTURE-BASED LEARNING TRAJECTORY IN IMPROVING MATHEMATICAL COMMUNICATION SKILLS OF SMA NEGERI 3 PADANG STUDENTS - Rani Rahim; Hasratuddin; Mukhtar (MATEMATIKA DAN PEMBELAJARAN, 2026)
This study aimed to implement a Minangkabau culture-based learning pathway and to improve students' mathematical communication skills at SMA Negeri 3 Padang. This study uses a design research approach with three phases (preliminary design, teaching experiment, and retrospective analysis), the study involved 36 students in the main teaching experiment after a pilot study involving 8 students. The learning trajectory integrated Minangkabau cultural contexts such as traditional house architecture, traditional textiles, and market systems into mathematics learning activities. The learning trajectory was implemented on transformational geometry topics (translation, reflection, rotation, and dilation). The results showed a significant improvement in students' mathematical communication skills, with the average score increasing from 62.3 (pre-test) to 84.7 (post-test). Students demonstrated improved abilities in expressing mathematical ideas orally and in writing, using mathematical representations, and interpreting mathematical statements. The culture-based learning trajectory proved effective in making mathematics more meaningful and relevant to students' daily lives.   Keywords: Design Research; Ethnomathematics; Learning Trajectory; Mathematical Communication; Minangkabau Culture